Constructivism-Based Mathematics Learning Multimedia to Improve Students’ Mathematical Communication Skills - Syukri, Ahmad; Marzal, Jefri; Muhaimin, Muhaimin (Indonesian Journal of Science and Mathematics Education, 2020)
This study aims to describe the process of developing Constructivism-based Mathematics Multimedia, determine students’ perceptions of Multimedia and find out the level of improvement in students’ mathematics communication skills after using this Multimedia. This research ran for 1 month in class X MIPA 1, X MIPA 2, and X MIPA 3 SMAN 1 Jambi. The development model used in this study is the ADDIE development model. The type of data is qualitative data and quantitative data. From the results of the pre-test and post-test, it was found that 13 students had an increase in mathematical communication skills with high criteria, 7 students had an increase in mathematical communication skills with medium criteria, and 12 students had an increase in mathematical communication skills with low criteria. Based on the results of the study it can be concluded that Constructivism-based Multimedia can improve the students’ mathematics communication skills.